Enhancing Indonesian EFL teachers’ literacy teaching strategies and professional learning through designing CLIL-based reading activities - Utami Widiati; Siti Muniroh; Niamika El Khoiri; Metaria Metaria; Muhimatul Murtafi'ah; Lina Hanifiyah; Tengku Intan Suzila Tengku Sharif (Studies in English Language and Education, 2026)
Developing learners’ literacy skills is one of the challenges faced by EFL teachers. This action research focuses on implementing content and language integrated learning (CLIL)-based reading activities to empower Indonesian EFL teachers in designing a basic literacy instruction in the form of in-class and out-of-class reading activities and to examine their professional learning experiences during the implementation of the action. Twenty secondary EFL teachers of a regency in East Java Province, Indonesia, participated in this research and engaged in 32-hour intervention activities comprising modelling, practice, reflection and action planning. CLIL aspects of cognition, content, communication, and culture were highlighted throughout the activities. The procedures of action research by Kemmis and McTaggart (2005) were conducted, covering the stages of planning, implementing, observing, and reflecting. Data was collected through field notes, lesson plan guidelines, and teacher reflective journals and qualitatively analyzed to examine how CLIL aspects were evident in the literacy activities and to what extent the 20 EFL teachers experienced professional learning during the study. The results of data analyses revealed that the teachers were empowered to design in-class and out-of-class reading activities by integrating the CLIL aspects into the activities. The action activities have also successfully helped teachers experience professional learning of designing various reading activities which can later be disseminated to their colleagues and students through their own action plans, supporting a focus on site-based practices and arrangements, an awareness of the learning complexity, and collaboration.